Família acolhedora e reintegração familiar: impasses e reflexões sobre a implementação de uma política pública para crianças e adolescentes - Ayla Bianca Silva Chaves (2019)
The Foster Family Service executes the foster care protective measure, being presented as an alternative in the protection of children and adolescents when rupturing with the institutionalization of these. Besides that, it would guarantee family coexistence and facilitate the process of family reintegration. The present study aimed to investigate whether family foster care constitutes a public policy that actually assists in family reintegration. For this, it was also aimed at discussing the academic productions and legislation involving the Foster Family; to analyze how the family is inserted in public policies; to discuss how the foster care program deals with the origin families. The foster is a public policy regulated and executed by equipment of the Single System of Social Assistance and the System of Guarantee of the Rights of the Child and the Adolescent, therefore it has the premise of decentralization, so each municipality has its own regulations. For the present work, the service of Belo Horizonte was studied in its practical and legislative peculiarities. The methodology used was the bibliographic review at four databases, namely, Index-Psi, PePSIC, Periódicos Capes and SciELo, using four descriptors: foster care, foster family, family reintegration and family reunification. The searches generated a total of 1.401 articles, after exclusion criteria 31 were chosen to compose the present research. Thematic content analysis was the chosen method of analysis. The articles found were divided into three categories, each with two subcategories, discussing: in the first category the structuring and performance of the family care services, in the second category the possibilities and limitations for the family coexistence and, finally, the detachment plan for the family reintegration and the post-reintegration experience. It is concluded that even with the Foster Family Service formats, in modalities and their prerequisites, families of origin may not have full access to children and adolescents nor to policies that can help them reverse or remedy the removal of offspring. Thus, one possibility that arises to support the families of origin is the subsidized guard. It is understood that investment in public policies should include support to the family of origin in order to corroborate what is prescribed in childhood / youth legislation regarding the priority for family reintegration.